The Effect of Mindfulness and Religious Coping on Elderly Mental Health - Itqoniah, Cut Fauziah; Adriani, Yufi (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
The elderly population continues to increase not only in the world, but also in Indonesia. One of the cities that contribute to increasing the number of elderly people in Indonesia is Depok, West Java. Elderly is a stage that has experienced many changes and faced various challenges in life. The elderly tend to experience a decline in various aspects. They experience changes in physical, psychological, and social aspects. The changes that occur and all the challenges that must be faced can have an impact on the physical, mental and functioning of life. This study aims to examine whether mindfulness and religious coping have an effect on the mental health of the elderly in Depok city. The sample used were 282 elderly people who were taken using a non-probability sampling technique, namely purposive sampling. The instruments used in this study are adaptations and modifications of the Mental Health Continuum-Long Form (MHC-LF), Five Facet Mindfulness Questionnaire (FFMQ) and Brief RCOPE instruments. The results showed that at 36.5%, there was a significant effect of mindfulness and religious coping together on the mental health of the elderly. In detail, the results of the minor hypothesis prove that there is a significant effect of three dimensions of mindfulness (observe, describe, and act with awareness) and one dimension of religious coping (positive religious coping) on the mental health of the elderly.